The Effect of Digital Literacy and Financial Literacy on Financial Behavior Case Study of Students at Terara State High School 1, Class of 2023 - Anggraeni, Baiq Nini Pratiwi; Wardani, Laila (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study explores how digital literacy and financial literacy contribute to shaping students’ financial behavior. Using a quantitative design with a structural model approach, data were collected through questionnaires to measure the influence of both literacy variables on financial decisions made by students. The findings reveal that digital literacy plays a crucial role in enabling students to use digital financial tools effectively, while financial literacy strengthens their ability to manage income, expenses, and financial risks. Both variables show a significant positive effect on financial behavior, indicating that students with higher literacy levels tend to behave more responsibly in managing personal finances. These results highlight the importance of integrating digital and financial education within the school environment to support students' financial readiness in the digital era.